Mizoroki-Heck reaction of 1,2-disubstituted aryl alkenes: variables of synthesis, solvent and ligand modulation of reactivity - Bangar, Pronnoy G.; Jawalkar, Priyanka R.; Dumbre, Swapnil R.; Raut, Pallavi K.; Patil, Dharmaraj J.; Tv, Neethu; Sudhakaran, Shana; Iyer, Suresh (Synthetic Communications, 2020)
Reaction of aryl iodides with 1,2-disubstituted aryl alkenes in the presence of TBABr/TBACl gave high yields of the Mizoroki-Heck product. Phosphine ligands were used for the modulation of reactivity and stereoselectivity, for the reaction of 4-iodoanisole with cinnamaldehyde. tert-Bu3P.HBF(4)gave the highest E:Z ratio of 1:0.08. The use of PEG-200 and PEG-400 as solvent could activate the reaction of aryl iodides with various 1,2-disubstituetd aryl alkenes.
Keywords: 12-Disubstituted aryl alkenes; 400; ligand effect; Mizoroki-Heck reaction; PEG 200; TBABr

Bimetallic Ni-Pd synergism-mixed metal catalysis of the mizoroki-heck reaction and the suzuki-miyaura coupling of aryl bromides - Kashid, Abhijit A.; Patil, Dharmaraj J.; Mali, Ramling D.; Patil, Vijay P.; Neethu, T. V.; Meroliya, Heena K.; Waghmode, Shobha A.; Iyer, Suresh (Catalysis Letters, 2021)
A combination of Pd and Ni complexes activated aryl bromides for the thermal Mizoroki-Heck reaction and Suzuki coupling giving high yields in short reaction times. A thermal redox mechanism probably occurs whereby Ni complex transfers electron and reduces the Pd (II) to Pd (0) which then takes the reactants through the standard protocol of oxidative-addition, migratory insertion and reductive elimination, typical for the Mizoroki-Heck reaction and the Suzuki coupling. [GRAPHICS] .
Keywords: Bimetallic catalysis; Mizoroki-Heck; Nickel complexes; Pd(OAc)2; Suzuki coupling

Bimetallic Ni–Pd synergism—mixed metal catalysis of the mizoroki-heck reaction and the suzuki–miyaura coupling of aryl bromides - Kashid, Abhijit A.; Patil, Dharmaraj J.; Mali, Ramling D.; Patil, Vijay P.; Neethu, T. V.; Meroliya, Heena K.; Waghmode, Shobha A.; Iyer, Suresh (Catalysis Letters, 2021)
A combination of Pd and Ni complexes activated aryl bromides for the thermal Mizoroki-Heck reaction and Suzuki coupling giving high yields in short reaction times. A thermal redox mechanism probably occurs whereby Ni complex transfers electron and reduces the Pd (II) to Pd (0) which then takes the reactants through the standard protocol of oxidative-addition, migratory insertion and reductive elimination, typical for the Mizoroki-Heck reaction and the Suzuki coupling.